Phenomenological-Communicative Review of OnlyFans Normalization on Twitter Media - Al-Mujtahid, Nazil Mumtaz; Zainun, Zainun; Efendi, Erwan (UNIVERSITAS PAKUAN, 2020)
This thesis aims to analyze and explore the communication phenomena related to the normalization of OnlyFans on Twitter. The dynamics of pornography on social media are a concerning issue. The emergence of several platforms has led to an escalation of pornography content accessible to the public. Moreover, pornography has become more intimate and personal with the advent of OnlyFans as a new type of transactional pornography on social media. The urgency of this research is to examine the OnlyFans normalization phenomenon using a communication perspective. This study employs a qualitative method with a field study approach. The research paradigm is critical with a media analysis context. The primary data source in this study are millions of Twitter user tweets indicating OnlyFans escalation, while the secondary data used are expert opinions, regulations, scientific articles, and books supporting the research. Data collection techniques include observation, interviews, documentation, and Focus Group Discussions (FGD). The collected data will then be analyzed using Miles and Huberman's techniques, which include data collection, data reduction, and conclusion drawing. Data validity testing is performed using triangulation techniques. The research findings show that the escalation of OnlyFans on Twitter has seen significant growth. In Indonesia, Twitter is used only for promotion by OnlyFans creators. Cumulatively, the sentiment that emerges tends to be neutral towards the presence of OnlyFans. However, this sentiment is not absolute as it brings concerns, such as: 1) Digital transformation of desires, 2) Shadow industry, 3) Risk of exploitation, 4) Pandora's box of desires, and 5) Social values. The dynamics of OnlyFans in Indonesia have spurred active discussions, sentiments, perceptions, promotions, ethics, and social norms. The communication phenomena arising from OnlyFans in this study include: 1) Democratization of pornography, 2) Destigmatization of sexuality, 3) Personalization of pornography, 4) Influence of social media, and 5) Debates and regulations. These phenomena can be mitigated through collective intelligence-based digital campaigns